Potencial Bankruptcy: Before and During Covid-19 Pandemic - Slamet Ahmadi; Susanti Widhiastuti (Politeknik Caltex Riau, 2023)
This study aims to analyze the Altman Z-Score, Springate, and Zmijewski theory in assessing the level of financial health and anticipating the problems of potential bankruptcy in the food and beverage sector before Covid-19 in 2019 and when Covid takes place in 2020. This study was conducted on 10 food and beverage companies with a score analysis method of the company's financial ratios for financial performance. The Altman Z-Score, Springate, and Zmijewski method use delivery services, profit, total assets, total debt, profit before interest and taxes, capital, and sales.The results showed that the company that is still classified as healthy but experienced a significant financial decline in 2020 is the bakery company, while the company that experienced a significant increase in 2020 is MYOR. Based on the Zmijewski score, all companies as the object of the study are healthy category that the score is <0.